PERANCANGAN ALAT TIMBANG UNTUK REKAPITULASI PEMAKAIAN ZAT PEWARNA KAIN DI PT. INDO-RAMA SYNTHETIC TBK. MENGGUNAKAN ARDUINO WEMOS LOLIN S2 MINI DENGAN MODUL LOAD CELL HX711 - Kurniawan, Andrea; Astriany Rizky, Ardelia (POLITEKNIK PIKSI GANESHA, 2024)
This research aims to design a weighing tool that can record the use of fabric dyes in the dyeing department of PT. Indo-Rama Synthetic Tbk. The author uses a case study research method which includes observation and interviews with staff. This weighing tool was built using hardware in the form of an Arduino WEMOS LOLIN S2 MINI as the controlling brain, a Load Cell with an HX711 module as a weight sensor, a 4x4 keypad used to provide instructions from the user and a 20x4 LCD display to display weighing results. Then PHP, HTML and CSS software to build website-based interface applications and the XAMPP application which functions as database management and PHP services. By using this weighing tool, dye consumption reports, which were previously done manually, can now be done automatically during the weighing process.